THE EFFECT OF DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH INCENTIVES AS A MODERATOR VARIABLE (AT THE CLASS I RAILWAY ENGINEERING CENTER FOR THE CENTRAL JAVA REGION) - Berkah Nadi, Muhammad Abi; Karunia, Meutia Nadia; Kurniawan, Ramdhan (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This research was conducted to see the effect of discipline and motivation on employee performance with incentives as a moderator variable (at the Class I Railway Engineering Center in the Central Java Region). The population in this study were 143 employees of the Class I Railway Engineering Center for the Central Java Region. The number of samples taken in this study was determined through a purposive random sampling method using the entire population of 143 employees of the Class I Railway Engineering Center, Central Java Region. The results of the research show that the discipline variable partially has a positive and significant effect on employee performance. This is evidenced by the value of the regression coefficient is 0.375 (positive) with a significance value of 0.002 <0.05, then H1 is accepted. The motivation variable partially has a positive and significant effect on employee performance. This is evidenced by the value of the regression coefficient is 0.253 (positive) with a significance value of 0.004 <0.05, then H2 is accepted. The variables of discipline and motivation simultaneously have a positive and significant effect on employee performance. This is evidenced by the calculated F value of 15.285 > F table of 4.01 and a significance value (Sig.) 0.000 <0.05, then H3 is accepted. The incentive variable moderates the relationship between discipline and employee performance. This is evidenced by the significant influence of the value of Y2 on Y1 on the first output and the interaction effect of X1*Y2 on the second output is significant, meaning that incentives as a moderating variable in the relationship between discipline and employee performance are quasi moderators, so H4 is accepted. Incentive variables moderate the relationship between motivation on employee performance. This is evidenced by the influence of the value of Y2 on Y1 in the first output which has a significant effect and the interaction effect of X2 * Y2 on the second output has a significant effect, meaning that incentives as a moderating variable in the relationship between motivation on employee performance is a quasi moderator, then H5 is accepted .